2020
DOI: 10.3390/nu12072136
|View full text |Cite
|
Sign up to set email alerts
|

To Wean or Not to Wean: The Role of Autologous Reconstructive Surgery in the Natural History of Pediatric Short Bowel Syndrome on Behalf of Italian Society for Gastroenterology, Hepatology and Nutrition (SIGENP)

Abstract: Pediatric Short Bowel Syndrome (SBS) can require prolonged parenteral nutrition (PN). Over the years, SBS management has been implemented by autologous gastrointestinal reconstructive surgery (AGIR). The primary objective of the present review was to assess the effect of AGIR on weaning off PN. We also evaluated how AGIR impacts survival, the need for transplantation (Tx) and the development of liver disease (LD). We conducted a systematic literature search to identify studies published from January 1999 to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…The impact of surgery on weaning off PN was assessed by a recent systematic literature review [122]. It found that surgery has low benefit in terms of intestinal adaptation and therefore it should not be proposed to all patients with SBS, but only to selected candidates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of surgery on weaning off PN was assessed by a recent systematic literature review [122]. It found that surgery has low benefit in terms of intestinal adaptation and therefore it should not be proposed to all patients with SBS, but only to selected candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Main requirements to refer for surgery should be radiologically evident bowel dilation associated with signs or symptoms of small bowel bacterial overgrowth, such as failure of advancing enteral nutrition and poor growth. Early signs of intestinal failure-associated liver disease (IFALD) should also be considered, if associated with intestinal dilation, as a factor in favor of eligibility for surgery [122].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There's not much recent literature that describes the outcomes or complications of LILT. The latest review on LILT sums up research showing that a patient has a chance of 55,5–100% to become PN independent within 2 years after undergoing a LILT procedure [ 3 ▪ ]. A recent single-center retrospective study by Shah et al shows similar results (5 out of 9 patients weaned off).…”
Section: Longitudinal Intestinal Lengthening and Tailoring (Lilt)mentioning
confidence: 99%
“…An elongation of on average 75% is achieved according to a recent analysis of 19 studies [ 3 ▪ ]. A comparative retrospective study showed an increase in length of 25 cm and initial feeding time of 8 days, however without differences in outcome compared to LILT [ 4 ].…”
Section: Serial Transverse Enteroplastymentioning
confidence: 99%